EFFECT OF PLICKERS-BASED DISCOVERY LEARNING ON LEARNING OUTCOMES IN SALT HYDROLYSIS AMONG CLASS XI MIPA STUDENTS AT SMA KARTIKA XX-1 MAKASSAR - Auliah, Army; Nurhaliza; Majid, Ahmad Fudhail; Cahyani, Vika Puji; Romadin, Achmad; Nawi, Mohd Zulfakar Mohd (Science Education, Institut Agama Islam Negeri Ponorogo, 2025)
Students are always faced with a saturated situation due to uninteresting and monotonous learning models and media. This causes students to pay less attention to the teacher's explanation and causes low student learning outcomes. One way to improve student learning outcomes is to use the Discovery Learning Model with the help of technology-based assessment tools, namely Plickers. The purpose of this research was to determine the effect of Plickers media in the Discovery Learning Model on the learning outcomes of Class XI MIPA students at SMA Kartika XX-1 Makassar. The research method used was quasi-experimental using a post-test only control group design. The research population was all classes XI MIPA SMA Kartika XX-1 Makassar with a total of six classes. The research sample was class XI MIPA 5 as the experimental class and class XI MIPA 4 as the control class. The data collection technique was carried out by giving a multiple-choice test with 20 validated items to obtain learning outcome data. Inferential statistical analysis used the Mann-Whitney test and obtained Zcount = 10.94 and the Ztable value at the 0.05 level of significance is 1.65. So that Zcount (10.94) > Ztabel (1.65), which means that the Plickers media in the Discovery Learning Model has an effect on participant learning outcomes. Class XI MIPA students at SMA Kartika XX-1 Makassar on the main material of salt hydrolysis.